Spatial Variation in Microbial Community in Response to As and Pb Contamination in Paddy Soils Near a Pb-Zn Mining Site - Zou, Lina; Lu, Yanhong; Dai, Yuxia; Khan, Muhammad Imran; Gustave, Williamson; Nie, Jun; Liao, Yulin; Tang, Xianjin; Shi, Jiyan; Xu, Jianming (Frontiers in Environmental Science, 2021)
Mining activity is a growing environmental concern as it contributes to heavy metal(loid)s (HMs) pollution in neighboring agricultural soils. Microbial communities play an important role in the biogeochemical cycling of HMs and have the potential to be used as bioindicators. Arsenic (As) and lead (Pb) are the most hazardous HMs and are mainly originated from mining activities. However, paddy soil microbial communities’ response to soil As and Pb pollutant remains overlooked. In this study, the biological and chemical properties of sixteen soil samples from four sites (N01, N02, N03, and N04) near a Pb-Zinc (Zn) mine contaminated with As and Pb at different levels were examined. The results showed that soil pH, total As and Pb, bioavailable As and Pb, nitrate-nitrogen (NO3--N) and ammonia-nitrogen (NH4+-N) were the most important factors in shaping the bacterial community structure. In addition, significant correlations between various bacterial genera and As and Pb concentrations were observed, indicating their potential roles in As and Pb biogeochemical cycling. These findings provide insights into the variation of paddy soil bacterial community in soils co-contaminated with different levels of As and Pb.